(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Online College Portal aims at providing the Facility to automate and simplify the smooth interaction between student and faculty. This application do all automated work regarding maintaining and disseminating all information which is extremely useful in colleges. The creation and management of accurate & update information regarding a student is critically important in college. The administrator and student are two major functional requirements in the given system. Proper login with time & role based secure access is provided to admin, faculty & students. The whole system will be controlled by admin. This portal includes forums, term-work management and uploading /downloading study material, exam schedule. All these general details like student name, address, performance, attendance etc provide various records regarding students. This application is helpful in sharing of document with the individual, department or whole organization depending on the requirement. Students do registration on college portal. The admin verify and accept request. All verified student can access the portal and participate in forum.